EFFECTIVENESS OF THE ELECTRONIC INVESTIGATION MANAGEMENT SYSTEM (E-MP) IN THE GORONTALO POLDA - Hendra J. Hasan; Ismet Sulila; Sukarman Kamuli (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This research aims to analyze and describe the effectiveness of the Electronic Investigation Management (E-MP) system at the Gorontalo Regional Police, examining the 5 (five) principles that must be fulfilled in policy effectiveness, namely: Right policy, Right implementation, Right target, Right environment, and Right process. The approach used in this research is qualitative. The research method is descriptive qualitative. Data collection was carried out using interview techniques, observation and documentation studies. The data analysis technique in this research was carried out by data reduction, data presentation and drawing conclusions/verification. The research results show 1) In terms of system accuracy indicators, E-MP has supported the duties and functions of investigations at the Gorontalo Regional Police; 2) The indicator of accuracy in implementing the E-MP system at the Gorontalo Regional Police shows that the system is being implemented properly in accordance with the initial objectives of the E-MP implemented at the Gorontalo Regional Police; 3) The E-MP target accuracy indicator at the Gorontalo Regional Police shows the success of the system with clarity of work targets as planned; 4) The environmental accuracy indicator of the E-MP system at the Gorontalo Regional Police shows that the internal environment is good with interaction between the National Police and the Gorontalo Regional Police through coordination and monitoring. However, the external environment is not yet good, public perception of the E-MP system at the Gorontalo Regional Police is not completely good due to lack of socialization; 5) The indicator of the accuracy of the E-MP system process at the Gorontalo Regional Police shows that the level of E-MP acceptance at the Gorontalo Regional Police is good. Personnel acceptance of E-MP as a useful rule and tool for drug investigations. The Narcotics Directorate and the public, especially suspects, can understand and accept all the rules that have been set. The Narcotics Directorate and the community are ready to be involved in implementing and being part of the implementation of the Electronic Investigation Management (E-MP) system at the Gorontalo Regional Police